2016
DOI: 10.3389/fncel.2016.00266
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Radical Scavenger Treatment of a Mouse Model of Rett Syndrome: Merits and Limitations of the Vitamin E Derivative Trolox

Abstract: Rett syndrome (RTT) is a severe neurodevelopmental disorder typically arising from spontaneous mutations in the X-chromosomal methyl-CpG binding protein 2 (MECP2) gene. The almost exclusively female Rett patients show an apparently normal development during their first 6–18 months of life. Subsequently, cognitive- and motor-impairment, hand stereotypies, loss of learned skills, epilepsy and irregular breathing manifest. Early mitochondrial impairment and oxidative challenge are considered to facilitate disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 87 publications
5
35
0
7
Order By: Relevance
“…The conducted redox analyses now confirm for the first time that the oxidative burden in RTT also applies to astrocytes. As we verified earlier, the free-radical scavenger Trolox improved the cellular redox balance in organotypic hippocampal slices [40], dampened neuronal hyperexcitability in adult hippocampal slices of symptomatic Mecp2 −/y mice, and also improved the hypoxia tolerance as well as certain types of synaptic plasticity [66, 67]. In these studies, any adverse impact of Trolox on mitochondrial function could be ruled out, and also here, an overnight incubation of astrocytes with Trolox did not affect mitochondrial shape or ΔΨm.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The conducted redox analyses now confirm for the first time that the oxidative burden in RTT also applies to astrocytes. As we verified earlier, the free-radical scavenger Trolox improved the cellular redox balance in organotypic hippocampal slices [40], dampened neuronal hyperexcitability in adult hippocampal slices of symptomatic Mecp2 −/y mice, and also improved the hypoxia tolerance as well as certain types of synaptic plasticity [66, 67]. In these studies, any adverse impact of Trolox on mitochondrial function could be ruled out, and also here, an overnight incubation of astrocytes with Trolox did not affect mitochondrial shape or ΔΨm.…”
Section: Discussionmentioning
confidence: 68%
“…Also, we previously confirmed that the vitamin E derivative Trolox improves cellular redox balance as well as synaptic function of the Mecp2 −/y hippocampus in vitro [40, 66], and it ameliorates some RTT symptoms when applied systemically to Mecp2 −/y mice [67]. Therefore, we assessed potential Trolox-mediated effects on mitochondrial function by incubating cell cultures overnight with this free-radical scavenger (100  μ M, 12–14 h).…”
Section: Resultsmentioning
confidence: 92%
“…Hypoxic conditions are often experienced in the form of intermittent hypoxia. It is a characteristic condition in patients suffering from obstructive sleep apnoea, familial dysautonomia (Weese-Mayer et al 2008a,b;Carroll et al 2012), Rett syndrome (Weese-Mayer et al 2006;Schüle et al 2008;Janc et al 2016), mitochondrial disease (Brown & Squier, 1996;Quintana et al 2012;Herst et al 2017), epilepsy (Cohen-Gadol et al 2004;Farrell et al 2016) and many other disorders characterized as 'dysautonomia' . These disorders are often associated with breathing disturbances, increased heart rate, decreased heart rate variability and other forms of disturbed cardiorespiratory coupling.…”
Section: The Effect Of Intermittent Hypoxia On the Cardiorespiratory mentioning
confidence: 99%
“…4; Viemari et al 2005). These mice and also human patients are characterized by increased oxidative stress (De Felice et al 2012Janc & Muller, 2014;Ciccoli et al 2015;Filosa et al 2015;Janc et al 2016;Pecorelli et al 2016). It is therefore conceivable that the oxidative stress seen after CIH also contributes to the breathing disturbances in Rett syndrome including the characteristic fluctuations in tidal volume (Fig.…”
Section: The Effect Of Intermittent Hypoxia On the Cardiorespiratory mentioning
confidence: 99%
“…The Mecp2 −/y mouse model of RTT shows a prominent respiratory phenotype that develops relatively late during postnatal development. At P40, breathing is more irregular and MeCP2-deficient mice show reduced respiratory rate and an increased number of longer breathing arrests (Janc et al, 2016 ). At this age, 5-ht 5b receptor expression in the medulla of Mecp2 −/y mice is still elevated while it drops to neonatal level in the WT littermates between P21 and P40 (Vogelgesang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%